EFFECT OF MANUAL THERAPY ON TEMPOROMANDIBULAR JOINT DISORDERS - Fazira, Elfa Risma; Santoso, Totok Budi (Ikatan Dosen Menulis, 2025)
This study aims to determine the effect of manual therapy on temporomandibular joint disorders. Using Single Subject Research (SSR) with A-B-A design, this study was conducted at the Griya Physiotherapy Colomadu clinic within two weeks with 24 subjects leading to TMJ disorders, 21 subjects did not experience TMJ disorders according to the inclusion criteria and 3 subjects experienced TMJ disorders according to the inclusion criteria. A therapy manual was given in the form of manipulation therapy in C0-C1, TMJ joint repositioning, mandibular exercise, and soft tissue release three times of therapy. Subjects were examined using the Quisionare Fonseca Anamnestic Index (FAI) and the data were analyzed using the analysis of non-overlapping data results or Percentage of Nonoverlapping Data (PND). Mr. R obtained an FAI result score of 80 at the beginning of the examination which means that it included the classification of severe TMJ disorder and after being given three interventions of therapy experienced a decrease in the FAI examination result score to 15 (no TMJ disorder), Mrs. S subject obtained an initial outcome score of 70 (severe TMJ disorder) after being given three times of therapy the final result score of FAI became 20 (mild TMJ disorder) and Mrs. I subject obtained an initial outcome score as many as 65 (moderate TMJ impairment) after being given three times of therapy, the FAI result score became 15 (without TMJ impairment). The results of the data analysis from each subject were Mr. R with a PND value = 100% (very effective), Mrs. S with a PND value = 100% (very effective) and Mrs. I with a PND value = 66.66% (moderate effect). Conclusion: based on the results of data analysis in this study, the effect of manual therapy (C0-C1 manipulation therapy, TMJ repositioning, mandibular exercise and release of soft tissue adhesions) as many as three times of therapy in three respondents or subjects succeeded in lowering the score of the criteria for severe TMJ disorder to mild TMJ disorder and without TMJ disorder, the results were different or not the same in each subject because there were still data analysis results that were still overlapping.